IMF Staff papers : Volume 42 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1995)
This paper provides a critical survey of the literature on politico-institutional determinants of the government budget. We organize our discussion around two questions: Why did certain OECD countries, but not others, accumulate large public debts? Why did these fiscal imbalances appear in the last twenty years rather than sooner? We begin by discussing the 'tax smoothing' model and conclude that this approach alone cannot provide complete answers to these questions. We then proceed to a discussion of political economy models, which we organize into six groups: (1) models based upon opportunistic policy makers and naive voters with 'fiscal illusion'; (2) models of intergenerational redistributions; (3) models of debt as a strategic variable, linking the current government with the next one; (4) models of coalition governments; (5) models of geographically dispersed interests; and (6) models emphasizing the effects of budgetary institutions. We conclude by briefly discussing policy implications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet